HISTORY OF THE DEVELOPMENT OF PENCAK SILAT TAPAK SUCI PUTERA MUHAMMADIYAH REGIONAL LEADER 143 KUNINGA N DISTRICT - Rudiana, Bambang; Oman Hadiana (STKIP Muhammadiyah Kuningan, 2024)
The aim of this research is to find out the history of the development and aspects of arts, martial arts and sports of Muhammadiyah men's holy sites in Kuningan. The method used is qualitative research. The sample in this study was 3 warriors, 3 cadres, 5 students. The sampling technique uses purposive sampling. The results of interview research show that the development of Tapak Suci Putera Muhammadiyah in Kuningan Regency was first established at SMK Negeri 3 Kuningan by an electricity teacher named Mr. Aam Muharam who came from Garut and invited one of his students who happened to be the head of the OSIS named Sueb. From a sporting aspect, it produces athletes who compete at the National Championship, World Championship and National Sports Week levels. In the artistic aspect, Tapak Suci has a national style typical of Tapak Suci which every warrior and cadre must know because that is the main requirement for advancing to the belt level. In the martial arts aspect, Tapak Suci Kuningan carries out training every Friday for cadres and warriors. The results of collecting observation data from the management and each training branch stated that not everyone was aware of the establishment of Tapak Suci in Kuningan. The results of the documentation data collection show that there is no book on the founding of Tapak Suci in Kuningan